2010
DOI: 10.1007/s11255-010-9769-9
|View full text |Cite
|
Sign up to set email alerts
|

Renal reserve in the oldest old

Abstract: Renal reserve is preserved in healthy very old people, but its magnitude decreases significantly with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
0
15
0
4
Order By: Relevance
“…Something similar was documented in the newborns but in this case it was attributed to tubular immaturity since this finding disappeared as they grew older [8,9] . Renal reserve is defined as the ability of the kidney of increasing its basal glomerular filtration rate in at least 20% after a proteic overload, it has been reported that it is preserved in the very old people, although its magnitude is considerably lower in comparison with the one in the young, since the increase in CC between its basal value (fasting) and its post-prandial highest one (peak) is significantly lower in the very old (40%) respect to the young (90%) (P = 0.02) [10][11][12] . Clinical consequences [13] : (1) It is worth mentioning that the characteristic of the reduced glomerular filtration in the very old is one of the factors which fosters medicine intoxication, if the doses were not adjusted to the glomerular filtration; (2) During pre-renal acute renal failure secondary to dehydration, serum creatinine and urea values are usually equally high due to an augment in the habitual creatine back-filtration in the aged.…”
Section: Creatinine Handlingmentioning
confidence: 99%
“…Something similar was documented in the newborns but in this case it was attributed to tubular immaturity since this finding disappeared as they grew older [8,9] . Renal reserve is defined as the ability of the kidney of increasing its basal glomerular filtration rate in at least 20% after a proteic overload, it has been reported that it is preserved in the very old people, although its magnitude is considerably lower in comparison with the one in the young, since the increase in CC between its basal value (fasting) and its post-prandial highest one (peak) is significantly lower in the very old (40%) respect to the young (90%) (P = 0.02) [10][11][12] . Clinical consequences [13] : (1) It is worth mentioning that the characteristic of the reduced glomerular filtration in the very old is one of the factors which fosters medicine intoxication, if the doses were not adjusted to the glomerular filtration; (2) During pre-renal acute renal failure secondary to dehydration, serum creatinine and urea values are usually equally high due to an augment in the habitual creatine back-filtration in the aged.…”
Section: Creatinine Handlingmentioning
confidence: 99%
“…This phenomenon has been attributed to tubular immaturity in neonates and to senile histological tubular changes in the elderly, such as tubular fatty degeneration, presence of diverticula, irregular thickening of their basal membrane, as well as increasing zones of atrophy and fibrosis (6)(7)(8)(9)(10)(11). All these senile changes could make proximal tubules more permeable and consequently more susceptible to creatinine back-filtration (4).…”
Section: Discussionmentioning
confidence: 99%
“…Найбільша відповідь відміча-ється на введення яловичого білка, дещо менша -соєвого і найменша -молочного [12] Згодом були запропоновані методики з введенням пацієнтам внутрішньовенно розчину білка [13] або амінокис-лот [14]. Також для більшої об'єктивізації результа-тів для усунення впливу секреції креатиніну в нир-кових канальцях застосовують додаткове введення циметидину [15]. Іншою методикою є проба із вве-денням низьких доз допаміну для збільшення вну-трішньониркового кровотоку і клубочкової філь-трації [16], можливе також поєднане застосування розчину амінокислот і допаміну [17].…”
Section: вступunclassified